Catechol-O-methyltransferase genotype is associated with plasma total homocysteine levels and may increase venous thrombosis risk - Gellekink, Henkjan; Muntjewerff, Jan-Willem; Vermeulen, Sita H. H. M.; Hermus, Ad R. M. M.; Blom, Henk J.; Heijer, Martin den (Thrombosis and Haemostasis, 2007)
A disturbed methylation has been proposed as a mechanism via which homocysteine is associated with diseases like vascular disease, neural tube defects and mental disorders. Catechol- O-methyltransferase (COMT) is involved in the S-adenosylmethionine- dependent methylation of catecholamines and catecholestrogens and in this way contributes to homocysteine synthesis. COMT dysfunction has been related to schizophrenia and breast cancer. We hypothesized that COMT dysfunction by virtue of functional genetic polymorphisms may affect plasma total homocysteine (tHcy). Our primary objective was to study the association between common COMT polymorphisms and tHcy. Secondly, we evaluated these polymorphisms as a risk factor for recurrent venous thrombosis. We obtained genotype data from four polymorphisms in the COMT gene (rs2097603, rs4633, rs4680 [324G>A] and rs174699) from 401 populationbased controls. We performed haplotype analysis to investigate the association between common haplotypes and tHcy. In addition, we assessed the rs4680 variant as a genetic risk factor in a case-control study on recurrent venous thrombosis (n= 169). We identified a common haplotype that was significantly associated with tHcy levels. This effect was largely explained by the rs4680 variant, resulting in an increase in tHcy of 10.4% (95% CI 0.01 to 0.21, p=0.03) for 324AA compared with 324GG subjects. Interestingly, we found that the 324AA genotype was more common in venous thrombosis patients (OR 1.61 [95% CI 0.97 to 2.65], p=0.06) compared to control subjects. We show that the COMT rs4680 variant modulates tHcy, and might be associated with venous thrombosis risk as well.
Keywords: Homocysteine; haplotype; catechol-O-methyltransferase; venous thrombosis